Development and Characterization of Hybrid Natural Fiber Reinforced Composites based on Poly- propylene Resin (International Journal of Engineering and Computer Science, 2015)
Recently natural fibers have been receiving considerable attention as substitutes for synthetic fiber reinforcements in plastics due to their low cost, low density, acceptable specific strength, good thermal insulation properties, reduced tool wear, reduced thermal and respiratory irritation and renewable resources. The development of natural fiber usage in India has now reached an appreciable stage. The present project work is taken up to develop a Natural Fiber Reinforced Composite material to get desired mechanical properties so that it can replace the existing Synthetic Fiber Reinforced Composite material for a suitable application.